Peningkatan Produktivitas Kinerja pada Universitas XYZ Menggunakan Metode Marvin E Mundel - Susiati, Devi; Pradana, Franky Rangga (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
The development of the world of education requires university institutions to continue to increase innovation and productivity so that they can be highly competitive. Factors that are very influential in improving the quality of the University are lecturers and students. For this reason, XYZ University must be able to adapt to technological developments so that it can respond quickly to global market needs. With this phenomenon, XYZ University, especially the Faculty of Engineering, needs skilled workers in the engineering field so as to produce graduates who have relevant abilities and skills. The current vision of the Faculty of Engineering is